The Effects of Single and Combined Repetitive Oral Administration of Common Pesticides and Alcohol on Rabbits (1999)
The toxicological effects of repetitive single or combined oral administration of a synthetic pyrethroid pesticide (KarateR), nicotine and alcohol (ethanol) in rabbits were studied. Rabbits given daily oral doses of either KarateR, nicotine or ethanol and a combination of either KarateR and nicotine or alcohol exhibited various forms and severities of nervous signs, haematological and serum biochemical alterations, and lungs, liver, heart, kidney and brain damage. Single repetitive nicotine consumption proved most fatal with 75% mortality rate recorded within eight weeks, while combined KarateR and alcohol consumption caused 100% mortality within ten weeks. Severe anaemia, panleucopenia, significant increase in serum gammaglutamyl transferase and hypocholesterolaemia were the hallmarks of severe toxicity with these agents. This study highlights the possible long-term effects of the indiscriminate use of pesticides, and some common environmental pollutants like alcohol on rabbits. This very serious threat to biodiversity Conservation efforts in our environment that may result from this is discussed.